2022
DOI: 10.3389/fneur.2022.841310
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hydrogen as a Medical Gas for the Treatment of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome: Possible Efficacy Based on a Literature Review

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a disorder that is characterized by fatigue that persists for more than 6 months, weakness, sleep disturbances, and cognitive dysfunction. There are multiple possible etiologies for ME/CFS, among which mitochondrial dysfunction plays a major role in abnormal energy metabolism. The potential of many substances for the treatment of ME/CFS has been examined; however, satisfactory outcomes have not yet been achieved. The development of new substances f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“… 11 12 A recent literature review revealed that H 2 attenuated acute or chronic fatigue in animals and healthy subjects. 13 We also reported that the anti-fatigue effects of H 2 involved the protection of mitochondria, which may also ameliorate the pathogenesis of ME/CFS. 13 Therefore, we conducted this case study to test this hypothesis by examining the efficacy of H 2 gas inhalation in four patients with ME/CFS.…”
mentioning
confidence: 81%
“… 11 12 A recent literature review revealed that H 2 attenuated acute or chronic fatigue in animals and healthy subjects. 13 We also reported that the anti-fatigue effects of H 2 involved the protection of mitochondria, which may also ameliorate the pathogenesis of ME/CFS. 13 Therefore, we conducted this case study to test this hypothesis by examining the efficacy of H 2 gas inhalation in four patients with ME/CFS.…”
mentioning
confidence: 81%
“…The findings further indicated that molecular hydrogen impeded NF-κB phosphorylation, leading to a significant reduction in inflammation. Moreover, Hirano et al highlighted the positive influence of molecular hydrogen on both acute and chronic fatigue in their review article . Growing evidence from animal models suggests potential long-term benefits of molecular hydrogen in treating stroke patients.…”
Section: Preclinical Study For the Development Of Stroke Treatmentmentioning
confidence: 99%
“…Moreover, Hirano et al highlighted the positive influence of molecular hydrogen on both acute and chronic fatigue in their review article. 32 Growing evidence from animal models suggests potential long-term benefits of molecular hydrogen in treating stroke patients. However, there is currently limited clinical evidence to confirm these prolonged advantages.…”
Section: Stroke Treatmentmentioning
confidence: 99%
“…Recently, symptoms similar to those of CFS have been reported in the sequelae of COVID-19 infection and SARS-CoV-2 vaccine [4,5,6], and the number of patients is gradually increasing worldwide. There are multiple possible causes of CFS, including abnormal energy metabolism due to mitochondrial dysfunction [7] and inflammation in the brain.…”
Section: Introductionmentioning
confidence: 99%